Pengaruh Green Innovation dan Carbon Emission Disclosure terhadap Kinerja Keuangan dimoderasi Gender Diversity - Mulya Rizki Putri; Rina Yuniarti; Ahmad Junaidi (Politeknik Ganesha Medan, 2025)
This study aims to examine the moderating role of gender diversity in the relationship between green innovation, carbon emission disclosure (CED), and financial performance. A quantitative approach was applied using secondary data from financial and sustainability reports of high-profile and low-profile companies listed on the Indonesia Stock Exchange (IDX) during 2023–2024. From a population of 738 firms, 177 were selected through purposive sampling, yielding 354 observations. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with WarpPLS 7.0. The results reveal that green innovation and CED have a positive and significant effect on financial performance, reflected in improved cost efficiency, reputation, sustainable financing access, and stakeholder trust. Furthermore, gender diversity strengthens the impact of green innovation and CED on profitability and corporate legitimacy. These findings highlight the importance of integrating sustainability strategies with balanced gender representation on boards to enhance financial performance and ensure long-term corporate sustainability. Practically, the study suggests that companies should reinforce green innovation, environmental disclosure, and gender diversity as synergistic strategies to achieve optimal performance.